2002
DOI: 10.1103/physrevb.65.201201
|View full text |Cite
|
Sign up to set email alerts
|

Coherent response of spin-orbit split-off excitons in InP: Isolation of many-body effects through interference

Abstract: The spin-orbit split-off ͑SO͒ exciton is observed in a III-V semiconductor ͑InP͒ using spectrally resolved four-wave mixing ͑SR-FWM͒ with 1.515 eV, 35 fs pulses at 77 K. Interference between the coherent response of the SO exciton and that of electron-hole pairs in continuum states leads to frequency-and time-dependent signatures that can be directly attributed to excitation-induced dephasing ͑EID͒ of the SO exciton. Many-body effects can therefore be isolated from free induction decay contributions, in contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…40,58,59 The interband response is characteristic of an inhomogeneously-broadened transition, 60,61 while the exciton signal is dominated by an interaction-induced nonlinearity related to exciton-carrier scattering. [41][42][43] As seen in Fig. 2(b), HT GaMnAs exhibits a similar four-wave mixing response to HT GaAs, reflecting the clean band structure in this sample.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…40,58,59 The interband response is characteristic of an inhomogeneously-broadened transition, 60,61 while the exciton signal is dominated by an interaction-induced nonlinearity related to exciton-carrier scattering. [41][42][43] As seen in Fig. 2(b), HT GaMnAs exhibits a similar four-wave mixing response to HT GaAs, reflecting the clean band structure in this sample.…”
supporting
confidence: 53%
“…The spectral content of this emission, together with its dependence on the time delay between the two exciting laser pulses, provides information regarding the density and nature of the electronic transitions, interactions within the excited carrier system, and the coherence decay time. [38][39][40][41][42][43] Four-wave mixing experiments are expected to provide a sensitive probe of Mn-related features in the electronic structure of III-Mn-V semiconductors, including the prevalence of defect-to-band transitions 27,33 and the influence of (s,p)-d hybridization on the valence states. 23,28 This sensitivity is tied to the nonlinearity of the technique, as the four-wave mixing polarization is proportional to the cube of the energy-dependent dipole matrix element.…”
Section: -19mentioning
confidence: 99%
“…A recent clear observation of the spin-orbit split-off ͑SO͒ exciton in a four-wave-mixing experiment has shown that nonlinear optical methods are very effective to study the properties of semiconductors in the spectral range far above the band gap. 4 The observation of the SO exciton in Ref. 4 was based on the fact that excitons strongly influence the coherent response of the semiconductor through the interference of exciton and continuum polarization sources.…”
Section: Introductionmentioning
confidence: 99%
“…A similar effect was observed in experiments at the spin-orbit split-off exciton in InP, where the role of the band tail continuum was played by interband transitions associated with the heavy-hole and light-hole valence bands. 35 We note that the smaller magnitude of the exciton response relative to the continuum in the LT-GaAs samples annealed at higher temperatures in comparison to the HT-GaAs sample is not clear but may reflect a change in the magnitude of the dynamically screened EID/EIS coefficients due to the residual disorder. Disorder in the crystal structure leads to local potential fluctuations and an associated quasicontinuum of weakly-bound energy states in the vicinity of the band extrema.…”
Section: -6mentioning
confidence: 97%
“…In previous FWM experiments on LT-GaAs, the exciton signal was identified as resulting from excitation-induced dephasing (EID), 28 through which non-degenerate Coulomb interactions of excitons with carriers excited on the interband continuum lead to diffraction of the exciton polarization from a grating in the total free carrier population. [32][33][34][35] Such an EID signal is only present at zero delay due to interference of signal contributions from population gratings over a broad range of …”
Section: -5mentioning
confidence: 99%